Legal regulation of foreign affairs governance: foreign experience for Ukraine - Zozulia, Oleksandr; Zozulia, Ihor; Dovhan, Olena (DIXI, 2023)
The organization of foreign affairs governance in different countries reveals differences in approaches to legal regulation in the status, competence, structure and principles of interaction of foreign affairs governance bodies. This is primarily due to the peculiarities of the form of government and the state system, the practice of public administration and current foreign policy goals. The advantages and shortcomings of the organization of foreign affairs governance in different countries should be one of the main sources of optimizing the foreign affairs governance of Ukraine. That is why the purpose of this article is to analyze the advantages and disadvantages of different approaches to the legal regulation of foreign affairs governance, to determine features of the legal status of subjects of foreign affairs governance in different countries, as well as to substantiate the priority areas for improving the organization of foreign affairs governance in Ukraine. This leads to the use of dialectical, formal-legal, comparative-legal, system-structural, logical-semantic and other scientific methods. Effective implementation of foreign policy requires a modern constructive organization of foreign affairs governance, taking into account the peculiarities of the state system, foreign policy interests and potential of the state, as well as progressive trends and positive experience of other states. Proper legal organization of foreign affairs governance should provide for its integration into a single system of public administration, centralization and hierarchical of the system of foreign affairs governance bodies, the system-forming role of the Ministry of Foreign Affairs, clear division of powers between it and higher authorities, professional diplomatic service etc.
Keywords: foreign policy; governance; legal regulation; Ukraine; foreign affairs